Physicochemical and sensory characterization of ‘Dekopon’ fruits - Siqueira, Ana Paula Silva; Vendruscolo, Eduardo Pradi; Vasconcelos, Luís Henrique Costa; Araújo, Isabela Rosa de; Seleguini, Alexsander (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2020)
Dekopon is a seedless tangor of expressive size and its harvest is not the same as Ponkan’s, which has been the most commercialized cultivar. The aim of this study was to characterize physico-chemically and sensorially this tangor, through evaluations of soluble solids, acidity, ratio, vitamin C, diameter, peel thickness, firmness, juice volume and sensory impressions on taste, appearance, aroma, texture, overall impression and purchase intention. High levels of vitamin C and the volume of juice which correspond to about 50% of the weight of the fruit stood out regarding the chemical attributes. Most of the scores attributed to 'Dekopon' were above 6.0 and the ones of purchase intention were above 3.0. The fruit can be considered promising to be commercialized due to its good characteristics.